A ESTIMULAÇÃO PRECOCE COMO UMA FORMA DE PREVENÃO E PROMOÇÃO DE SAÚDE DA PESSOA HUMANA - Soares da Silva, Danielle; Viana Amorin Kelly, Gésika; Laia Machado, Kelly; Fernandes Ramos dos Santos, Mariana (LINKSCIENCEPLACE, 2026)
Child development is a multiprofessional process that begins with the birth that encompasses physical growth and neurological, behavioral, cognitive, social and affective maturation of the child. From 0-3 years the brain develops rapidly, constituting an opportunity for the establishment of functions aiming independence and autonomy, where it is necessary that there is greater playful stimulation through play and actions of collectivity. Being the play a way of access of its importance in this prevention and health promotion, because it stimulates the potential of each child in the office and the natural environment, in the direction of type, speed of stimuli, that provoke reaction, potentiates parents and responsible in the interaction, communication, affection, preventing emotional disturbances and kinesthetic diseases and guides parents and community in a feeling of involvement and belonging. Increasingly, actions are needed to stimulate the child and broaden their abilities, addressing the stimuli that interfere in their maturation, to foster motor and cognitive development, focusing on social relations and playing, as a way to prevent psychiatric conditions as well as promote treatment within this reality, if the play is the direct access to the child is in the play that the treatment is structured.